2005
DOI: 10.1097/01.tp.0000164348.16689.03
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Inflammation Before and After Renal Transplantation

Abstract: Compared with controls, patients displayed an inflammatory phenomenon before receiving RT. Serum CRP decreased significantly after RT, whereas TNFalpha and IL-6 increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 26 publications
5
32
2
Order By: Relevance
“…21 Another study showed decreased levels of IL-6 and TNF-α after transplant compared with the baseline values; CRP levels were decreased at 6 months and increased at 12 and 18 months after transplant. 22 In the present study, IL-6 and hsCRP levels significantly decreased, but TNF-α and PTX-3 did not change after transplant (Table 2 and Figure 1).…”
Section: Discussionmentioning
confidence: 63%
“…21 Another study showed decreased levels of IL-6 and TNF-α after transplant compared with the baseline values; CRP levels were decreased at 6 months and increased at 12 and 18 months after transplant. 22 In the present study, IL-6 and hsCRP levels significantly decreased, but TNF-α and PTX-3 did not change after transplant (Table 2 and Figure 1).…”
Section: Discussionmentioning
confidence: 63%
“…The IL-6 data are more difficult to assess across diverse populations because of lack of standardized methods (31). However, in the posttransplant recipients, the inflammatory markers CRP and IL-6 have been reported to be elevated in most studies on renal transplant recipients (19,(21)(22)(23)(32)(33)(34)(35)(36), although they are lower than pretransplant values (37).…”
Section: Discussionmentioning
confidence: 99%
“…This has been reported in some studies for levels of C-reactive protein, TNF-alpha, and interlukin-6. 33 Another contributing factor may be a lessening of left ventricular hypertrophy after transplant. Such improvement may decrease the risk of mortality from coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%